Penambahan Tepung Tulang Bandeng (Chanos Chanos) Dalam Pembuatan Kerupuk Sebagai Hasil Samping Industri Bandeng Cabut Duri The Addition of Bone Milkfish (Chanos chanos L.) Flour in Making Crackers as Side Product of Boneless Milkfish Industry - Salitus Salitus; Dyah Ilminingtyas; Ery Fatarina (FEB UNTAG Semarang, 2017)
The development of bone crackers milkfish had quite big chance since it was apart from being an alternative waste handling might also increased the economic value of thorns fish, as well as improved the taste and nutritional value, especially calcium. This study aims was to determine the effect of the amount of milkfish bone flour addition for physical properties, chemical properties and preference level of panelists to bone crackers milkfish.The design of research used CRD (completely randomized design) with the addition of four treatment concentration of milkfish bone (K0 = addition of 0% milkfish bone flour, K1 = addition of 10% milkfish bone flour, K2 = addition of 15% milkfish bone flour and K3 = addition of 20% milkfish bone flour). Each treatment was repeated three times. It used Analysis of Variance (ANOVA) for calculating the of each treatment. If there were differences among the treatments then to knew which significantly different a further test using DUNCAN test was done. The collected data was calculated by SPSS 21 program software.The addition of milkfish bone flour in the crackers milkfish bone flour processing affected the level of crackers development (115.49% - 327.35%) and the brightness level (65.81% - 77.08%) but had no effect in the level of hardness (1476.17 gf - 3531.17 gf).The addition of milkfish bone flour in the crackers milkfish bone flour affected ash content (3.58% - 7.50%), fat content (21.52% - 32.41%), protein content (1.80% - 6.71 %), carbohydrates (34.43% - 37.83%), calcium levels (0.02% - 1.17%) but had no effect in the water content (1.51% - 2.31%).The addition of milkfish bone flour influenced the color preference level by panelists (4.16 to 5.33) but not for the flavor (4.83 to 5.32), aroma (4.35 to 4.84) and texture (4.68- 5.25) of crackers.